Enhancement of Germination and Seedling Health of Rice by Seed Treatment with Antagonist Fungi - Deb, Subash Chandra; Khair, Abul (International Journal of Scientific Research in Biological Sciences, 2020)
Germination and seedling health is important for effective crop establishment. Application of Aspergillus spp. and Trichoderma spp. is the alternative way of intensified germination and healthy seedling production in the crop field. Rice seeds were coated with a spore mass of antagonists showed a significant increase in seed germination and healthy seedlings production compared to the control. At the same time leaf infection, collar infection, root infection, and seedling blight symptoms also decreased remarkably. The highest germination and healthy seedling were recorded 80.33% and 74.37% respectively by T. harzianum treatment. Seeds were subjected to soaking with three water-based culture filtrates (30%, 50%, and 70%) obtained from both three species of Aspergillus and Trichoderma (A. flavus, A. niger, A. terreus, T. viride, T. harzianum, T. hamatum) for 6, 12 and 24 hours. The highest reduction of fungal associations and increased germination was observed 36% and 79.33% respectively in T. harzianum treatment compared to untreated control. The effect was more prominent at the highest dose (70%) and the maximum seed soaking period (24 hours). Apart from all antagonist treatments test fungicide Tilt 250 EC depicted excellent control effect (22.0%). A. niger and T. harzianum were found more potent in reducing seed-borne fungal association as well as improved germination and seedling health.